O ativismo e a necessidade de autocontenção do Poder Judiciário - Cândido, Carlos Henrique (2021)
Considering the Brazilian Federal Supreme Court as guardian of the Constitution, this research starts from the hypothesis that the burden to have the last word about what the constitutional norms say does not authorize the Judiciary to deliver activist responses, always with the scope of a constitutional rule, even in hard cases, nor does it remove the need for justifications of decisions based on scientifically verifiable legal techniques. The central discussions on the theme are inspired by the comparison of the different thesis defended by Streck (contrary to activism), in contrast to those of Barroso (favorable). In this factual and legal context, the scope was limited to the debate about activism and its implications in a scenario characterized by the constitutionalization of law amid constitutionalism. Bringing the topic to discussion from a consistent doctrinal counterpoint and pointing out methodologies that enable the necessary differentiation of activist decisions from those resulting from cases of judicialization of politics is the contribution of this work to society and especially to the academic environment. The results were achieved based on the premise that law as a science, built on a theory of decision constructed from the Dworkin teachings, is sufficient to justify judicial responses at the expense of conduct activists. In addition, the judicialization of politics, although inexorable, is defended as contingent and, because it is inevitable, it is argued that the resulting response may need special treatment based on the mitigation of its rigidity. The methodology used is predominantly deductive: to achieve the results, the bibliographical references were used, comparing the counterpoints about activism, judicialization, hard cases, constitutionalization and constitutionalism, in addition to their respective summarized historical contexts, set as premises for the development of the theme and to arrive the conclusion that the subject is current and lacks doctrinal debates and normative delimitations, based on the juxtaposition of the arguments and related themes, while it points to law as science and the deconstitutionalization of law-decision as proposals for tackling judicial activism and giving back the power to decide to the majorities.